Understanding Organizational Commitments in the Public Sector: A Case Study of Commissioners and Investigators at The Business Competition Supervisory Commission (KPPU) - Yogi Sumarsana Wibowo; Muchlis R. Luddin; Eliana Sari (Indonesian Association for Public Administration, 2019)
Considering that KPPU is the only institution that handles law enforcement in the field of business competition, it is necessary to have high employee commitment and organizational strength. This study aims to explore the commitment of KPPU’s commissioner and investigator organizations. This research is a qualitative design study of a case study. The data were collected from interviews with six commissioners and twenty-one investigators. This study found that the commitment of commissioners and investigators to achieving the vision and mission in the field of law enforcement has been indicated by the emotional ties and involvement with the organization through the egalitarian principles instilled by the previous commissioners. The commitment of the commissioners and investigator is built on the agreement that the place of dedication realize ideas and contributions to the state in improving people’s welfare that is appropriate. By considering these findings, KPPU needs to strengthen its internal function of supervision to maintain high organizational ethics, integrity, and independence in performing its tasks. Considering the organizational culture, KPPU needs to build a higher levels of public service motivation to get a greater organizational commitment.